Challenges for gatekeeping: a qualitative systems analysis of a pilot in rural China - Jin Xu; Anne Mills (BMC, 2017)
Abstract Background Gatekeeping involves a generalist doctor who controls patients' access to specialist care, and has been discussed as an important policy option to rebalance the primary care and hospital sectors in low- and middle-income countries, despite thin evidence. A gatekeeping pilot in a Chinese rural setting launched in 2013 has offered an opportunity to study the functioning of gatekeeping under such conditions. Methods In this qualitative study within a mixed-method evaluation of the gatekeeping pilot, we developed an innovative systems analysis method, combining the World Health Organisation categorisation of health system building blocks, the "Framework" approach of policy analysis and causal loop analysis. We conducted in-depth interviews with 20 stakeholders from 4 groups (patients, doctors, health facility managers and government administrators) in the pilot area over two years. Based on information extracted from the interviews, we drew a causal loop diagram which highlighted the feedback loops within the system that had self-reinforcing or self-balancing characteristics, and used the diagram to examine systematically the mechanisms of intended and actual functioning of gatekeeping and analyse the systems level challenges that affected the effectiveness of gatekeeping. Results Had the gatekeeping pilot programme worked as intended, it would incentivize both providers and patients to increase service utilization at primary care level, as well as establish and enhance two reinforcing feedback loops to shift balance towards primary care. However, a performance-based salary policy undermined the motivation for clinical primary care. Furthermore, the primary care providers suffered from three reinforcing feedback loops (related to primary care capacity, human resource sustainability, patients' faith) that trapped primary care development in vicious cycles. At the interface between hospitals and primary care providers, there were also feedback loops exacerbating the existing hospital dominance. These feedback loops were intensified by the unintended consequences of concurrent policies (restrictions on technologies and medicines) and delayed reform in hospitals. Furthermore, the gatekeeping policy itself faced resistance to further development, due to the prevailing ineffective and ritualistic nature of gatekeeping, which formed a balancing loop. Conclusions The study shows that the intended benefits of gatekeeping were illusionary largely due to weak and worsening primary care conditions, and delay, ineffectiveness or unintended consequences of several other ongoing reforms. One particularly dangerous development of the system, which deserves urgent attention, is the harming of the professional prospects of primary care doctors. Our findings highlight the need for coordination and prioritization in designing policies related to primary care and managing changes with multiple on-going reforms. The approach used here facilitates comprehensive study of intended and actual mechanisms, and demonstrates the challenges of a complex health system intervention in a dynamic environment.